Tra Edipo ed Antigone: Archeologia del soggetto e apertura narrativa del sé secondo Paul Ricœur - Casucci, Marco (B@belonline, 2021)
The essay aims at investigating the evolution of the tragic symbol in Ricœur’s thought between Oedipus and Antigone. The prevalence of the Oedipus Tyrannos, particularly in the first period of the ricœurian reflection, oriented towards a critique of the Freudian interpretation, is balanced by a rediscovery of the Antigone’s “tragic of action” as it is well exposed in the Interlude of Oneself as Another. On the other hand, in the last Ricœur’s work, The Course of Recognition, the figure of Oedipus, as it is narrated in the last Sophoclean tragedy, the Oedipus Coloneus, rises again as a prototype of self-recognition. Thus, the tragic figures of Oedipus and Antigone are experienced by the ricœurian thought in different times and at different levels, reflecting its evolution through the different ages of Ricœur himself, showing the connection between the topic of tragedy and the narrative dimension of the self.